Canine Lymphoma, More Than a Morphological Diagnosis: What We Have Learned about Diffuse Large B-Cell Lymphoma - Aresu, Luca (Frontiers in Veterinary Science, 2016)
Diffuse large B-cell lymphoma (DLBCL) is the most common canine aggressive B-cell lymphoma worldwide and new recent molecular approaches have shown that DLBCL constitutes a heterogeneous tumor that cannot be unraveled by morphology and immunophenotype. DLBCL typically is an aggressive behaving lymphoma, evolving over months and the therapy response may be difficult to be predicted despite the clinical stage has been demonstrated to be prognostic. Transcriptomic analysis by gene expression profile, copy number variations by oACGH and epigenetic perturbations have tentatively described this heterogeneity. Molecular subgroups using oncogenic pathways and target genes have been also correlated to different outcome in a small number of cases. The objectives of this review are to summarize the current knowledge on the biology, clinical and pathological characteristics of canine DLBCL. To date, DLBCL probably is the most investigated tumor in veterinary medicine and it’s relevance as spontaneous model for human DLBCL has been confirmed by these studies. In future, these discoveries will ultimately lead to a better understanding a better understanding of the underlying disease mechanisms is translating into more effective therapeutic strategies.